Fault location in distribution system based on voltage sag analysis / Muhamad Firdaus Ahmad - Muhamad Firdaus , Ahmad (2020)
Fault in the distribution system is something that cannot be avoided. It is a recurring event that occurs due to various factors such as natural occurrence, mechanism failure, or human error. All this contributes to the phenomenon that will affect the stability of the system and result in the loss of power to the consumers. However, such a fault is something that happens unexpectedly, and it is difficult to be eliminated. Therefore, various research work has been done over the years to overcome the problem. All research is done to find the most effective method of finding the fault location in a short time. In this thesis, a way of identifying a fault location in the distribution system by using the voltage sag measurement is presented. The approach is to match the actual voltage sag magnitude with the stored database from the simulated fault. Any matching data will provide a possible fault section. Simulation result shows that it is possible to identify the fault location based on the analysis of the voltage sags.